Meta Analisis: Problem Based Learning (PBL): Hasil Riset - M. Dino Parlaungan; Irfan Firdaus; Prilia Padila; Nazaruddin Nazaruddin; Cahaya Amergus; Sair Sodikin; Zulfah Zulfah (Lembaga Penelitian dan Pengabdian Masyarakat, 2022)
The purpose of this study is to improve the mathematical problem solving ability of students who are taught by applying a problem based learning model that is taught by a direct learning model. Problem Based Learning (PBL) approach can be used as a solution in learning mathematics. The research method used is a quasi-experimental research in the form of a posttest and there is an experimental class and a control class. This research method is a meta-analysis with a sample of 5 articles in Sinta 3-6 accredited national journals from 2017 to 2021 with the research subject being junior high and high school education levels. Meta-analysis research shows that the effect of Problem Based Learning (PBL) learning approach is effective on problem solving abilities. The research data were collected through the provision of instruments in the form of a mathematical problem solving ability test in the form of description questions and observation sheets. The data analysis technique used descriptive statistics and inferential statistics. Based on the results of the study, it was concluded that there was a significant effect of the Problem Based Learning model on mathematical problem solving abilities.